The relationship between servant leadership, organizational citizenship behaviour, and dysfunctional turnover - Hin, Chow Wong; Sri Ramalu, Subramaniam; Chuah, Francis (Canadian Center of Science and Education, 2019)
The purpose of this conceptual paper is to provide a framework to enhance the understanding of factors that influence the turnover rate among high performers in an organization. The focus of this proposed conceptual framework is the study of the relationship between leadership style, organizational citizenship behaviour, and dysfunctional turnover. Based on literature reviews, evidences reveal a negative relationship between servant leadership and dysfunctional turnover which is mediated by the variable of organizational citizenship behaviour. From a practical standpoint, this paper provides additional knowledge in the area of dysfunctional turnover which can assist the relevant stakeholders in an organization to reduce brain drain and enable HR practitioners to have a better understanding on how to reduce turnover rate among high performers; whilst at the same time, contributing to the existing number of valuable researches that provide the much-needed knowledge in understanding the turnover phenomenon. Hence, there is a need to conduct an empirical based study to validate the proposed conceptual framework and to ascertain the relationship among the various variables in this framework.